ANALISIS MINAT PENGGUNA OVO DI JAKARTA SELATAN(STUDI PADA GENERASI MILENIAL PENGGUNA OVO) - Sari Tasnia, (2020)
This research is a quantitative study that aims to determine the effect of the variable ease, trust, and sales promotion on buying interest. The population in this study is OVO e-wallet users. The size of the sample taken by researchers as many as 75 respondents, with the probability sampling method, simple random sampling. Data collection was carried out through questionnaires. The analysis technique used is the PLS (Partial Least Square) analysis method with SmartPLS software. The results of this study indicate that (1) the convenience variable significantly influences the interest of OVO users with a path coefficient of 0.607 which means it has a positive relationship direction. (2) The trust variable influences the interest of OVO users in South Jakarta with a path coefficient value of 0.503 which means it has a positive relationship direction. (3) the variable of sales promotion has a significant effect on buying interest in OVO with a path coefficient value of - 0.212 which means it has a negative relationship direction. Keywords: Ease, Trust, Sales Promotion, and Buying Interest